Photovoice: A Tool of Reflective Learning to Enhance Students' Speaking Ability - Amirah Husnun; Aprilia Wulandari; Atika Munawwaroh; Nur Arifah Drajati (IAIN Salatiga, 2018)
Students tend to do the same mistakes when performing an oral speaking test. Due to the lack of students' skill in performing speaking, it triggers the researchers to raise this issue so the problem of students in performing speaking could be solved by using reflective learning based on reflective learning strengths. Narrative inquiry is used in this research to elaborate the method, in order to find and analyze the data, photovoice in which more practical is needed by collaborating with SHOWeD analysis. The participants of this study are 15 students who join speaking class of English Education Department. This article provides the findings of the use of reflective learning in the classroom to gain students' speaking ability for college students. In conclusion, the use of reflective learning from lectures to enhance students' speaking ability could be achieved through a certain treatment during the learning and teaching process.Keywords: Reflective Learning; Speaking Ability; Narrative Inquiry; Photovoice.